2015
DOI: 10.3329/bjms.v14i2.20272
|View full text |Cite
|
Sign up to set email alerts
|

The features of psycho-vegetative disorders and their role in the pathogenesis of gastroesophageal reflux disease with obesity

Abstract: Abstract:Background: Gastroesophageal reflux disease (GERD) is a disease of the XXI century, affecting the population in the developed countries. There is a clear tendency to increasing of gastroesophageal reflux disease among people of young age. Aim: The aim of the study is to determine the characteristics and role of psychosomatic and vegetative state disorders in the pathogenesis of GERD with concomitant obesity. Materials and methods: 50 young patients with GERD were examined during the study. Depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In its turn, this article studied and revealed the presence of a higher level of depression in patients with comorbid pathology compared to isolated one, and anxiety -in GERD with insomnia. In addition, the quality of life in patients with GERD was studied [2,23]. At the same time, we have shown that the combination of GERD with NCD and insomnia significantly reduces the indicators of the SF-36 scale, in comparison with isolated pathology.…”
Section: Discussionmentioning
confidence: 97%
“…In its turn, this article studied and revealed the presence of a higher level of depression in patients with comorbid pathology compared to isolated one, and anxiety -in GERD with insomnia. In addition, the quality of life in patients with GERD was studied [2,23]. At the same time, we have shown that the combination of GERD with NCD and insomnia significantly reduces the indicators of the SF-36 scale, in comparison with isolated pathology.…”
Section: Discussionmentioning
confidence: 97%
“…Among the many factors impacting the genesis of the motility and evacuation disorders in the upper gastrointestinal tract, disorders of neurohumoral regulation are of particular importance. Melatonin and serotonin play a special role in the mechanisms of these disorders [52,59]. The recent data on the effects these regulatory hormones have on gastrointestinal organs suggest an important role they play in the control over compensatory-adaptive processes and immune homeostasis in the gastric mucosa [60].…”
Section: Introductionmentioning
confidence: 99%